Angela and Diabola - Banks, Lynne Reid (HarperCollins Publishers Ltd, 1997)
Wicked, hilarious magic in an acclaimed novel of good and evil twins, from The New York Times bestselling author of The Indian in the Cupboard.Twins Angela and Diabola are as different as day and night. From the moment they are born, Angela is beautiful, loving, and perfect in every way. Diabola is ugly, unpleasant, and troublesome in direct proportion. No one knows what to do about the horrid child, and only her twin Angela has the power to affect her -- but at a terrible price.
Keywords: Juvenile literature-Babies-Behavior-Sisters-Twins-Fiction